An assessment of the leadership ability of public secondary school librarians in Valenzuela City - Dar Juan, Elijah John F. (2007)
Based on the premise that leadership is an influential factor in the development of school libraries in Valenzuela City. Specifically, the study aims to determine if these librarians possess leadership qualities as defined by the Leadership 20/20 Survey by Edwards and Ewen. Skills in which the librarians are competent, and incompetent is also investigated. The profile of each librarian is gathered to determine if there is a significant relationship between leadership ability and the librarians' demographic and professional data.